A contextual model for assessing the nexus between green innovation practices and enterprise performance - Takyi, Kwabena Nsiah; Gavurova, Beata; Asamoah, Comfort Adebi (Journal of Business Economics and Management, 2024)
The pursuit of green innovation and sustainable practices is increasingly growing currently because of the alarming environmental concerns and the coexistence of economic expansions. But the strategies employed by companies in exploring green innovation activities have gained little or no attention in literature. This study proposes a conceptual model that outlines green innovation strategies, corporate performance, and the moderating effect of green dynamic capacity. Based on the perspective of the Resource Based viewpoint and the notion of dynamic capabilities, this study addresses a) what is the relationship between green innovation practices and enterprise performance? and b) to what extent do green dynamic capabilities moderate the connection between green innovation practices and enterprise performance? We used a cross-sectional data from SMEs in Ghanaian manufacturing firms, analysed utilizing the advanced PLS-SEM systematic procedures. Our findings revealed a significant relationship between green product innovation, green process innovation, and green service innovation on financial performance and that green dynamic capacity moderate these relationships. Our research contributes to expanding the knowledge of green innovative practices among SMEs in the manufacturing sector. These findings have both theoretical and practical implications, opening numerous options for further research.